Analisis Pemikiran Umar bin Khattab Tentang Pengguguran Hak Mu’allaf sebagai Mustahiq Zakat - Muhammad Syaifudin (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
In the reign of Khulafaurrasyidin, the fourth caliph no longer provide the right of mu’allaf to the beneficiary, relying on Umar who flatly refuse to give alms to the rights of mu’allaf in the reign of Abu Bakr, and his reign. In fact, since the time of the Prophet they continue to receive zakat. This is where Omar issued a statement of law, that the al-mu’allafah qulubuhum not get the zakat, which none of the companions who opposed it. So opinions of Umar is a statute (ijma’) of the Companions and considered abrogatedpart mu’allaf. This paper studies about The reason of Umar bin Khattab did not provide the right of zakat to the mu’allaf as mustahiq of zakat, and how contemporary scholars put Umar thoughts about abortion right of mu’allaf as mustahiq of zakat in fiqh science literatures. The results of this research are, First, Umar bin Khattab abort asnaf rights for “al-mu’allafah qulubuhum” as a recipient of Zakat is due to the existence of a ‘illat (the reasons behind the solutions and decisions) that the state of “weak faith”. Second, the science of fiqh repertory, contemporary scholars put the Umar thoughts as a basis of ijtihad with the provision if the spirit of the background (‘illat law) is still visible, then the provisions of law applicable